Enterprise Mac administrator's guide - Edge, Charles S.; Hunter, Beau.; Smith, Zach. (New York, N.Y. : Apress, 2009)
"Charles Edge, Zack Smith, and Beau Hunter provide detailed explanations of the technology required for large-scale Mac OS X deployments and show you how to integrate it with other operating systems and applications"--
Includes index.
"The complete guide to Mac OS X administration"--Cover.
Keywords: Mac OS; Operating systems (Computers); Computer Science / IT